Molecular markers of artemisinin resistance during falciparum malaria elimination in Eastern Myanmar - Thu, AM; Phyo, AP; Pateekhum, C; Rae, JD; Landier, J; Parker, DM; Delmas, G; Watthanaworawit, W; McLean, ARD; Arya, A; Reyes, A; Li, X; et al. (BioMed Central, 2024)
Background: Artemisinin resistance in Plasmodium falciparum threatens global malaria elimination efforts. To contain and then eliminate artemisinin resistance in Eastern Myanmar a network of community-based malaria posts was instituted and targeted mass drug administration (MDA) with dihydroartemisinin-piperaquine (three rounds at monthly intervals) was conducted. The prevalence of artemisinin resistance during the elimination campaign (2013–2019) was characterized. Methods: Throughout the six-year campaign Plasmodium falciparum positive blood samples from symptomatic patients and from cross-sectional surveys were genotyped for mutations in kelch-13—a molecular marker of artemisinin resistance. Result: The program resulted in near elimination of falciparum malaria. Of 5162 P. falciparum positive blood samples genotyped, 3281 (63.6%) had K13 mutations. The prevalence of K13 mutations was 73.9% in 2013 and 64.4% in 2019. Overall, there was a small but significant decline in the proportion of K13 mutants (p < 0.001). In the MDA villages there was no significant change in the K13 proportions before and after MDA. The distribution of different K13 mutations changed substantially; F446I and P441L mutations increased in both MDA and non-MDA villages, while most other K13 mutations decreased. The proportion of C580Y mutations fell from 9.2% (43/467) before MDA to 2.3% (19/813) after MDA (p < 0.001). Similar changes occurred in the 487 villages where MDA was not conducted. Conclusion: The malaria elimination program in Kayin state, eastern Myanmar, led to a substantial reduction in falciparum malaria. Despite the intense use of artemisinin-based combination therapies, both in treatment and MDA, this did not select for artemisinin resistance.